Genetic Algorithm-Based Receiving Resonator Array Design for Wireless Power Transfer - Sasatani, Takuya; Narusue, Yoshiaki; Kawahara, Yoshihiro (IEEE access, 2020)
Deploying 2-D arrays of multiple transmitters is a promising approach for extending wireless power transfer (WPT) to wide surfaces. However, these arrays involve "null zones," where the transfer efficiency drops significantly. Although this problem can be hypothetically addressed by employing a receiver array and dynamically selecting the appropriate transmitter/receiver pair, designing receiver arrays that achieve high efficiency throughout the surface remains a challenging task. In this study, we propose a genetic algorithm (GA)-based approach to designing receiver arrays free of "null zones". The main objective is enhancing worst-case scenarios, which in contrast to improving best-case scenarios, reveals significant complexities due to the need for considering numerous possible placements. We overcome this problem by establishing a design flow that leverages the simulated transfer efficiency at numerous positions throughout the surface. Our approach increased the simulated transfer efficiency at the worst position from 3.8% to 42.6%, and we confirmed these results through measurements at the extracted points.